Cesarean delivery Characteristics during JKN Implementation : Karakteristik persalinan sesar selama Implementasi JKN - Sofia Al Farizi; Ernawati Ernawati; Erna W. Ernawaty (Indonesian Journal of Obstetrics and Gynecology, 2022)
Objective: To compare the characteristics of cesarean before and during JKN, also analyzes the factors that influence these differences. Methods: This was a quantitative study with a longitudinal retrospective design and qualitative research used design case studies. The population were delivery women at the Banyuwangi referral hospital before and during JKN. The quantitative data were analyzed firstly by univariable and then bivariable. The bivariable analysis was performed by comparing the prevalence ratio (PR) between two variables. Results: The proportion of cesarean delivery had increased significantly during the implementation of JKN. 50% of maternal deaths before JKN gave birth using cesarean delivery, this proportion increased significantly to 60% during JKN. Indications of fraud committed by health workers to be a factor in increasing the proportion of cesarean delivery. Other contributing factors were repeated cesarean delivery, delayed referral, and the number of obstetric complications. Conclusion: There was an increase in the proportion of cesarean deliveries during the implementation of JKN. BPJS Kesehatan needed to re-evaluate the system they had created so far. The quality of service must be emphasized so that the negative impact on women could be minimized. Keywords: cesarean section, health insurance, maternal mortality. Abstrak Tujuan: Membandingkan karakteristik persalinan sesar sebelum dan selama implementasi JKN, selain itu juga menganalisis faktor-faktor yang berpengaruh. Metode: Studi kuantitatif dengan desain longitudinal retrospective dan studi kualitatif dengan desain case studies. Populasi adalah ibu bersalin di rumah sakit rujukan Kabupaten Banyuwangi sebelum dan selama JKN. Data kuantitatif dianalisis secara univariabel dan bivariabel. Analisis bivariabel dengan membandingkan prevalensi rasio (PR) diantara dua variabel. Hasil: Proporsi persalinan sesar meningkat secara signifikan selama implementasi JKN. 50% ibu yang meninggal bersalin dengan metode sesar, proporsi ini meningkat selama JKN menjadi 60%. Indikasi kecurangan oleh tenaga kesehatan menjadi salah satu faktor yang menyebabkan peningkatan ini. Faktor lain yang berkontribusi adalah persalinan sesar yang berulang, keterlambatan rujukan dan banyakanya komplikasi obstetrik. Kesimpulan: Terdapat peningkatan proporsi persalinan sesar selama implementasi JKN. BPJS Kesehatan perlu mengkaji ulang sistem yang dibuat selama ini. Kualitas pelayanan harus tetap dipertahankan, agar tidak berdampak pada kesehatan ibu. Kata kunci: jaminan kesehatan, kematian ibu, persalinan sesar.